Filling the intervention gap: service evaluation of an intensive nonsurgical weight management programme for severe and complex obesity. Issue 3 (22nd November 2018) - McCombie, L.; Brosnahan, N.; Ross, H.; Bell‐Higgs, A.; Govan, L.; Lean, M. E. J.
Abstract: Background: Weight management including formula total diet replacement (TDR) is emerging as an effective intervention for severe and complex obesity, particularly with respect to type 2 diabetes (T2DM). However, no prospective audit and service evaluation of such programmes have been reported. Methods: Following initial feasibility piloting, the Counterweight‐Plus programme was commissioned across a variety of healthcare providers. The programme includes: Screening, TDR (formula low energy diet), food reintroduction and weight loss maintenance, all delivered by staff with 8 h of training, in‐service mentoring, ongoing specialist support and access to medical consultant expertise. Anonymised data are returned centrally for clinical evaluation. Results: Up to December 2016, 288 patients commenced the programme. Mean (SD) baseline characteristics were: age 47.5 (12.7) years, weight 128.0 (32.0) kg, body mass index 45.7 (10.1) kg m −2, n  = 76 (26.5%) were male and n  = 99 (34.5%) had T2DM. On an intention‐to‐treat (ITT) basis, a loss of ≥15 kg at 12 months was achieved by 48 patients, representing 22.1% of all who started and 40% of those who maintained engagement. For complete cases, mean (95% confidence interval) weight loss was 13.3 (12.1–14.4) kg at 3 months, 16.0 (14.4–17.6) kg at 6 months and 14.2 (12.1–16.3) kg at 12 months (all P  <   0.001), with losses to follow‐up of 10.8%, 29.3% and 44.2%, respectively. Mean loss at 12 months by ITT analyses was: single imputation –10.5 (9.5) kg, last observation carried forward –10.9 (11.6) kg and baseline observation carried forward –7.9 (11.1) kg. The presence of diabetes had no significant impact on weight change outcomes. Conclusions: This nonsurgical approach is effective for many individuals with severe and complex obesity, representing an option before considering surgery. The results are equally effective in terms of weight loss for people with T2DM.